DEALING WITH KANO MODEL DYNAMICS: STRENGTHENING THE QUALITY FUNCTION DEPLOYMENT AS A DESIGN FOR SIX SIGMA TOOL - Hendry Raharjo (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2007)
Six Sigma has been known to be a breakthrough business strategy to achieve customer satisfaction through defect reduction and cost optimization. A flawless product or service would, however, be of little value if it does not sell. Thus, it is of considerable importance to begin with the customer. Quality Function Deployment (QFD), as a customer-driven tool in Design for Six Sigma (DFSS) toolset, can be regarded as one of the most powerful tools to serve this purpose. The success of QFD use relies heavily on the accuracy of the primary input, that is, the Voice of the Customer (VOC). To better identify and obtain more accurate VOC, the use of Kano Model in QFD has been incorporated in the literature. Unfortunately, the dynamics of Kano Model, such as the fact that what now delights the customer will become an expected need in the future is often oversimplified and has not been adequately addressed. The aim of this paper is to shed some light to Kano Model dynamics modeling by providing a quantitative technique which is based on compositional data analysis. It is expected that a timely update of customer needs data may serve as a useful indicator to monitor the progress of how well a company satisfies its customer over time, and at the same time provide a ground for formulating the next strategies as to enable the company to respond differently and continuously over time of its operations. To give some practical insights, an illustrative example is provided.